Implementation of Hexacopter for Package Delivery - Wayan Suparta; Asmalia Che Ahmad; Asniza Hamimi Abdul Tharim (Majlesi Journal of Electrical Engineering)
This paper presents the engineering design of an unmanned aerial vehicle (UAV)/drone hexacopter and optimizes the PID (Proportional-Integral-Derivate) values for the Pixhawk 2.4.8 (PX4) flight controller. The design phase begins with component selection and identification, with the goal that the drone can carry loads up to 3 kg. Then install the main components and test the construction results. An analysis of the experimental results of the PID PX4 controller with no load and with load was performed. Results from direct field experiments with a home-built hexacopter show that the default PID must be tuned to be able to lift a load with a specific target.